PEMBELAJARAN PENJUMLAHAN BILANGAN PECAHAN DENGAN METODE CONTEXTUAL TEACHING AND LEARNING (CTL) DI SD MUHAMMADIYAH PROGRAM KHUSUS, KOTA BARAT, SURAKARTA - Hidayati, Yulia Maftuhah (Jurnal Penelitian Humaniora, 2012)
This study is aimed to describe the lesson plan, teaching learning process of sum of fractions based of Contextual Teaching and Learning (CTL), and the motivation of learners attend classes in learning. This study used a qualitative approach. The type of research is a case study. Validation of data is done through triangulation. Data were collected through interviews, observation, documentation, and testing. The technique of data analysis is descriptive, entrepretative. The results of this study indicate that (1) the development of lesson plan has been implemented routinely in every new school year, (2) the process of learning mathematics goes through three stages, namely preinstructional phase (preliminary / initial activity), instructional phase (core activities), and appraisal, (3) during the learning process, the students have a high motivation to participate in activities  because of the method used by teachers is fun and enjoyable